Effects of AM Fungi and Plant Growth-promoting Rhizobacteria on Enzymatic Activities of Soil under Turmeric (Curcuma longa L.) Cultivation - and Bijoy Neog, Shanti Chaya Dutta (Journal of the Indian Society of Soil Science, 2016)
Rhizomes of turmeric (Curcuma longa L.) are widely used for their medicinal as well as flavoring properties and in order to concentrate on biological means of promoting turmeric cultivation in Assam, a greenhouse experiment was conducted to evaluate the effects of native arbuscular mycorrhizal fungi (Glomus, Gigaspora and Acaulospora sp.) sourced from turmeric rhizosphere along with phosphate solubilizers (Bacillus megaterium) and nitrogen fixers (Azospirillum amazonense and Azotobacter sp.) on soil enzyme activities and microbial characteristics of soil under turmeric cultivation. The single, dual and consortium inoculations showed higher enzyme activities over control. Results revealed an increase in phosphatase (18.3–21.3 µmol p-nitrophenol g-1 h-1), dehydrogenase (83.4–100.5 nmol TPF g-1 h-1) and urease (83.2–99.5 µmol NH3-N g-1 h-1) enzyme activities along with an increase of 1.30–1.82 µg g-1 soil microbial biomass carbon content. Besides, mycorrhizal colonization rate showed a similar pattern in dual and consortium inoculation with single inoculation of arbuscular mycorrhizal fungi (95.2–97%) suggesting the plant growth promoting microbes as mycorrhiza helper bacteria for a clear preference as bioinoculants to be used for a sustainable agricultural strategy.